Pengendalian Internal, Asimetri Informasi, Integritas, Dan Budaya Organisasi Pada Kecurangan Akuntansi - Rajeswari, Ida Ayu Nadia Asawista; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 32 No 6 (2022), 2022)
This study aims to determine the effect of internal control, information asymmetry, integrity, and organizational culture on accounting fraud at PT. Regional Development Bank Bali Klungkung Branch Office. The research sample was 52 respondents using purposive sampling method. Technical analysis of the research using multiple linear regression analysis. The results of the study show that internal control, integrity, and organizational culture have a negative effect on accounting fraud, while information asymmetry has a positive effect on accounting fraud. The study provides input implications for considering the placement of employees in accordance with their competencies in each work unit in an effort to minimize the occurrence of accounting fraud. Keywords: Accounting Fraud; Internal Control; Information Asymmetry; Integrity; Organizational Culture.